Analysis of Fabry- Perot Cavity Design of Antenna and Its Radiation Characteristics Using Method of Moments - Krishna Mohan; Dr. K. B. Singh (International Journal of Scientific Research in Science and Technology, 2026)
In this present paper, we studied about Fabry-Perot Cavity design of Antenna and its radiation characteristics using method of moments (MoM).
Keywords: Antenna; Metal Strip Grating; Fabry-Perot Cavity; Microstripline